International students’ education for global peace: Insights from master students of international media studies at the Deutsche Welle Academy, Germany - Egielewa, Peter Eshioke; Ngonso, Blessed Frederick; Nwankwo, Udochukwu Chidi; Ebrima, Fadera; Ukhurebor, Kingsley Eghonghon (International Journal of Innovative Research and Scientific Studies, 2024)
This study examines international students’ education for global peace. Students who leave their home countries for educational tourism abroad encounter several challenges: a language barrier, cultural, ethical, and different educational systems, amongst others. Studies have shown that many international students face many challenges because of the need to interact in their new environment; these include communication problems (language), culture shock, the adaptation of value changes, and adjustment to new or completely different ethical principles, amongst others. Hence, this study investigates how 27 international students from 5 continents and 23 countries at the Master’s Programme “International Media Studies” (IMS) at the Deutsche Welle Academy in Bonn, Germany, who graduated in 2016, communicated, collaborated, and peacefully coexisted during their two years of studies. Based on the mixed research method and the instrument of the questionnaire, the study is anchored on the symbolic interactionism theory. Findings show that American and African students were the fastest to adjust to an international setting. Findings also reveal that American students are the most optimistic about the IMS programme helping to promote global peace, while African and European students are less optimistic. The study recommends that African and Asian international students should learn more about the culture of the host country when they travel abroad for studies, especially on issues of politeness, patience, and tolerance, and international students, in general, should understand the ethical issues surrounding giving tips when they travel abroad for studies.